The functions of teacher code switching in classrooms, and teachers’ perceptions towards this practice : a case study of siSwati-English interactions in a semi-urban high school in Eswatini - Stromvig, Hlobsile (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.